(untitled) (Gaceta Técnica, 2021)
The purpose of this research is to describe the statistical behavior and determine the probability distributions that best fit each of the components of conventional concrete mixtures, which are water, cement, fine aggregate and coarse aggregate, designed by the Porrero and ACI methods for compressive strengths between 250 and 280 Kg/cm2 with nominal maximum size of 1,0 inch, settlements up to 6,0 inches, Portland cement type I or type CPCA1 and natural sand. For this purpose, it was necessary to build a database under the consultation of degree theses elaborated in the Dean of Civil Engineering of the Universidad Centroccidental Lisandro Alvarado, 228 degree works were reviewed of which 66 complied with the established scope. The descriptive statistical analysis reported low and intermediate dispersions, it was concluded that the arithmetic mean obtained represents the data set by variable and the distributions obtained for water, cement, fine aggregate and coarse aggregate were Gen. Gamma (4P), Gen. Extreme Value, Weibull (3P) and Frechet respectively for the ACI method and for that of Porrero Hypersecant, Log-Pearson 3, Johnson SB and Chi-Squared (2P) as appropriate.